Review Journal: Analysis Of Side Effects Of Hormonal Contraception (Pil And Injection) - Hajar Hartati; Salman Salman; Indah Laily Hilmi (Sean Institute, 2023)
Contraception is a method used in the government's efforts to organize a Family Planning or “Keluarga Berencana” (KB) program. Contraceptives available in Indonesia are divided into hormonal contraceptives (pills, injections, and implants) and non-hormonal contraceptives such as IUDs or intra uterine devices. Of these two types of contraception, Indonesian people, especially women who use contraception, prefer hormonal contraception compared to non-hormonal contraception because it is considered more comfortable and easy to use. Among the three types of hormonal contraceptives, pills and injections are among the most widely used. However, in choosing between injections or birth control pills, some people are sometimes confused about which one to choose because they consider the side effects of both. So in this literature review, the authors compared the side effects between birth control pills and birth control injections from several existing journals. The results stated that there was no significant difference between the side effects of birth control pills or birth control injections and the duration of use was one of the factors that influenced the occurrence of side effects, especially the side effect of weight gain. So to overcome these side effects, the acceptors are expected to change the type of contraception if they have used >5 years and are advised to use non-hormonal contraception